Above Ground Biomass and Carbon Estimation on Pine Stands in Holcim Educational Forest Post Silica Mining Area PENDUGAAN KANDUNGAN BIOMASSA DAN KARBON ATAS TANAH PADA TEGAKAN PINUS DI LAHAN PASKA TAMBANG SILIKA HOLCIM EDUCATIONAL FOREST - Berry Oktavianto; Basuki Wasis; Sri Wilarso Budi R. (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
There are several factors affecting plant biomass, carbon stock, CO2-equivalent, and oxygen production (net O2 release), such as plant species (chlorophyll quality and leaf area), plant age, temperature, sunlight and land quality (water and nutrient availability). To estimate how much reclamation activity in post mining area has succeed in restoring plant biomass, carbon stock, CO2-equivalent, and net O2 release, especially post silica mining, a study to measure Pinus merkusii biomass, carbon stock, CO2-equivalent, and net O2 release planted in the area is undertaken. The study took place in Holcim Educational Forest (HEF) post silica mine reclamation area and Gunung Walat Education Forest (HPGW) as comparison site (non-reclamation). There are two age classes of Pinus merkusii being studied, those planted in 2005 and 2012. Study result shows that biomass of pine stand planted in 2005 on HPGW non-reclamation area is higher than on HEF reclamation area. The same result also occur on carbon stock, CO2-equivalent, and net O2 release measurement. However on the contrary, pine stand planted in 2012 on HEF reclamation area, have higher biomass compared with pine stand planted in 2012 on HPGW. The same result also occur on carbon stock, net O2 release and CO2-equivalent measurement, which is higher on pine stand planted in 2012 on HEF reclamation area. Overall soil quality analysis result, especially macro nutrient and micro nutrient, shows that on both site and both stand ages have relatively low macro nutrient content, except for high Mg content on 2012 pine stand in HPGW non reclamation area and very high S-available content in HEF reclamation area on both age classes. All micro nutrient analysis shows that on both age classes and on both area have medium micro nutrient content, except for very low Al content and very high Mn content.Key words: biomass, carbon stock, Pinus merkusii, reclamation, soil quality